Flexible biodegradable lemon juice based ionic polymer membrane. (2022) - Mohanty, Sribidhya; Panwar, Varij
Abstract: Ionic polymer membrane are highly efficient in the field of wearable devices, energy storage, biomedical devices, Thin Film Transistors (TFT) and energy separators. In all these applications high dielectric strength along with conductivity is needed. The previously available ionic polymer membrane used toxic electrolytes. In this paper, we present and analyse a PVA based lemon juice based ionic polymer membrane. The proposed membrane has good dielectric constant, better conductivity along a band and less dissipation factor with resonance in frequency range of 20 Hz to 10 MHz. In this paper PVA/Lemon Juice of 6 ml showed a good dielectric constant of 10 7, conductivity that increases with frequency and the generates resonance at a band of 10 3 to 10 5, This membrane generates low dissipation factor. In this paper we have presented a nontoxic flexible ionic polymer with lemon juice which is feasible for various ionic polymer applications. The best sample here we concluded is PVA/Lemon juice of 6 ml that showed good dielectric strength with balance conductivity and low dissipation factor. The conductivity increased upto 8 ml lemon juice after that the conductivity decreased. The proposed membrane is a nontoxic ionic polymer which is flexible, dielectric and conductive in nature making it suitable for wearable devices, TFT, energy storage, biomedical devices.